Wellbeing and occupational risk perception among health care workers: a multicenter study in Morocco and France. Issue 1 (December 2016) - Giurgiu, Doina; Jeoffrion, Christine; Roland-Lévy, Christine; Grasset, Benjamin; Dessomme, Brigitte; Moret, Leila; Roquelaure, Yves; Caubet, Alain; Verger, Christian; Laraqui, Chakib; Lombrail, Pierre; Geraut, Christian; et al.
Abstract Background The study analyzes health care workers' (HCWs) occupational risk perception and compares exposure to occupational risk factors in Moroccan and French hospitals. Method Across nine public hospitals from three Moroccan regions (north, center and south), a 49 item French questionnaire, based on the Job Content Questionnaire, and 4 occupational risks subscales, was distributed to 4746 HCWs. Internal consistency of the study was determined for each subscale. Confirmatory factor analysis was conducted on the Moroccan questionnaire. Psychosocial job demand, job decision latitude and social support scores analysis was used to isolate high strain jobs. Occupational risks and high strain perception correlation were analyzed by univariate and multivariate logistic regression. A comparative analysis between Moroccan and French (Nantes Hospitals) investigations data was performed. Results In Morocco, 2863 HCWs (60 %) answered the questionnaire (54 % women; mean age 40 years; mean work seniority 11 years; 24 % physicians; 45 % nurses). 44 % Moroccan HCWs are at high strain. Casablanca region (1.75 OR; CI: 1.34–2.28), north Morocco (1.66 OR; CI: 1.27–2.17), midwives (2.35 OR; 95 % CI 1.51–3.68), nursing aides (1.80 OR; 95 % CI: 1.09–2.95), full-time employment (1.34 OR; 95 % CI 1.06–1.68); hypnotics, sedatives use (1.48 OR; 95 % CI 1.19–1.83), analgesics use (1.40 OR; 95 % CI 1.18–1.65) were statistically associated to high strain. 44% Moroccan HCWs are at high strain versus 37 % French (Nantes) HCWs (p < 0.001). Conclusion Moroccan HCWs have high strain activity. Moroccan HCWs and more Moroccan physicians are at high strain than Nantes HCWs. Moroccan and French's results showed that full time workers, midwives, workers using hypnotics, and analgesics are at high strain. Our findings underscore out the importance of implementing a risk prevention plan and even a hospital reform. Further research, with an enlarged study pool will provide more information on psychosocial risks (PSR) and HCWs' health.